Pemanfaatan Lahan Tidur melalui Penanaman Nilam di Desa Kosambi Kecamatan Benua Kabupaten Konawe Selatan, Provinsi Sulawesi Tenggara - Sapto Raharjo; Tien Tien; A Kadir La Ode (Jurnal Gema Ngabdi, 2020)
Kosambi is a rural area, located in a high altitude area which belongs to Benua, South Konawe Regency, South East Sulawesi Province. The population is self-help transmigration from the province of South Sulawesi. Kosambi villagers generally burn and / or cut down forests to obtain land that will be used as planting areas. The land is not directly cultivated, but it is left first while collecting capital. This condition has the potential to cause erosion, and forest fires. Through the service funding scheme, the internal Community Partnership Program of Halu Oleo University in 2018 has successfully cultivated ¼ hectares of idle land from total of 2 hectares. Land management is performed through a partnership with patchouli farmers. At this initial stage, the land is only planted with patchouli. Patchouli planting patterns are arranged well so that the photosynthesis process occurs optimally. After six months, in August 2019, the first harvest was carried out. In the first harvest, 15 kg patchouli oil produced with a selling price of Rp. 505,000,- per kilogram. This year, cocoa planting will be tried as a protective crop in the new area planted with patchouli. Patchouli and cacao tree planting programs are expected to generate maximum farmer income in the future